적외선을 이용한 멀티 터치와 터치 인터페이스의 구현 - 유기선; 홍록지; 문일영; Yoo, Ki-Sun; Hong, Rok-Ji; Moon, Il-Young (한국항행학회논문지, 2010)
In this paper, the method introduce for touching signals and run the application on the multi touch environment using infrared light. When the user touches the screen, the infrared camera make a movie the light and the light which made through image processing communicate from TUIO(Tangble User Interface Object) protocol to Application. this Program is using the delivery informations which are occurred the event to Application. The Application which use the touch can exchange the Andoroid Phone between Mobile picture supervision Application also this equipment introduces about the musical entertainment Application which play a music many users at the same time. 본 논문에서는 적외선 빛을 이용하여 터치를 인식하고 어플리케이션을 구동할 수 있는 방법에 대하여 소개한다. 화면에 터치하면 그 곳의 빛을 적외선 카메라가 촬영을 하고, 촬영된 영상은 영상처리를 통해 ID, 좌표 등을 구한 후 TUIO Protocol로 Application에 통신 한다. 전달된 정보를 통해 Application에서 이벤트를 발생하여 구동하게 되는 원리이다. 본 논문에서는 터치를 이용한 Application은 Android Phone과 사진을 주고받을 수 있는 모바일 사진 관리 Application, 여러 사용자가 동시에 합주를 할 수 있는 음악연주 Application에 대해 설명한다.